Epigenetics and Vascular Diseases: Influence of Non-coding RNAs and Their Clinical Implications - Elia, Leonardo; Quintavalle, Manuela (Frontiers in Cardiovascular Medicine, 2017)
Epigenetics refers to heritable mechanisms able to modulate gene expression that do not involve alteration of the genomic DNA sequence. Classically, mechanisms such as DNA methylation and histone modifications were part of this classification. Today, this field of study has been expanded and includes also the large class of non-coding RNAs (ncRNAs). Indeed, with the extraordinary possibilities introduced by the next-generation sequencing approaches, our knowledge of the mammalian transcriptome has greatly improved. Today, we have identifying thousands of ncRNAs, and unsurprisingly, a direct association between ncRNA dysregulation and development of cardiovascular pathologies has been identified. This class of gene modulators is further divided into short- and long-ncRNAs. Among the short-ncRNA sub-group, the best-characterized players are represented by highly conserved RNAs named microRNAs (miRNAs). MiRNAs principally inhibit gene expression, and their involvement in cardiovascular diseases has been largely studied. On the other hand, due to the different roles played by long-ncRNAs, their involvement in cardiovascular pathology development is still limited, and further studies are needed. For instance, in order to define their roles in the cellular processes associated with the development of diseases, we need to better characterize the details of their mechanisms of action; only then might we be able to develop innovative therapeutic strategies. In this review, we would like to give an overview of the current knowledge on the function of ncRNAs and their involvement in the development of vascular diseases.